The Criminalization of Young Children and Overrepresentation of Black Youth in the Juvenile Justice System - Abrams, Laura S. (Race and social problems, 2021)
The American juvenile justice system is characterized by the overrepresentation of youth of color that is particularly acute for Black children even at young ages. Despite policy solutions targeting this problem, the Black-White gap in juvenile justice involvement continues to widen. Using mixed methods, this study examines rates of disproportionality among younger children (under age 12) in the state of California juvenile justice system alongside stakeholder views on the causes of and solutions for overrepresentation. We find that at each stage of the juvenile justice system the overrepresentation of Black youth increases relative to White youth. Consistent with the literature, stakeholders attribute this problem to early phases of the system (i.e., school discipline, arrests) where more discretion is applied. They also suggest that alternatives to formal systems involvement would help to remedy overrepresentation. These findings lend support to minimum age laws that uniformly exclude younger children from the juvenile justice system altogether.